Development and Application of Eco Enzyme for Household Organic Waste Management in Kampung Lio Area, Depok - Nufus, Tatun Hayatun; Saidatuningtyas, Ifa; Arnanda, Rachmat; Ardhan, Dhea Tisane; Khoirunnisa, Ratna; Garjati, Vina Nanda (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
Organic food waste accounts for the largest category of waste, comprising 40.8% according to data from the National Waste Management Information System (SIPSN). The high volume of this waste encourages alternatives for utilizing and processing household waste. One alternative method is producing an eco-enzyme, a liquid resulting from the fermentation of leftover fruits and vegetables. Its numerous uses and benefits have led to eco-enzyme development as an alternative method for processing household organic waste. To introduce this method, a Community Service (PKM) activity themed 'Development and Application of Eco Enzyme for Household Organic Waste Management' was conducted in the Kampung Lio area, Depok. This activity aims to enable the residents of Kampung Lio, Depok, to process their organic waste into eco enzyme and utilize it for various daily needs, such as floor cleaner, vegetable and fruit wash, insect repellent, plant fertilizer, disinfectant, laundry soap, bath soap, shampoo, toilet cleaner, and many other uses. After this activity, all participants started to implement their knowledge by processing their household organic waste into an eco enzyme because it has many benefits and simultaneously processed household waste.